Siderite and ferric oxyhydroxides imply interlinked carbon, iron, and halogen cycles on Mars - Kaushik Mitra; Lauren A. Malesky; Michael T. Thorpe; Ana Stevanovic (Proceedings of the National Academy of Sciences, 2025)
Pure siderite [Fe II CO 3 ] was recently discovered in abundant quantities (4.8 to 10.5 wt.%) by the Curiosity rover at Gale crater, Mars. Diagenetic alteration of siderite likely caused the carbonate-sequestered CO 2 to be released back into the atmosphere and consequently produced ferric [Fe(III)] oxyhydr(oxide) minerals. Here, using laboratory experimentation, we demonstrate that while closed system acid diagenesis—as proposed for Gale crater—is incapable of effective siderite alteration in Mars-relevant fluids, oxyhalogen compounds (chlorate and bromate) can weather siderite not only at acidic pH but also in near-neutral Mars-relevant solutions. The ferric oxyhydroxide minerals produced as a consequence are controlled by the diagenetic fluid composition. While photooxidation is possible, the mutually exclusive products of alteration—magnetite (Fe 3 O 4 ) during ultraviolet irradiation and ferric oxyhydroxide (FeOOH) by oxyhalogens—demonstrate that siderite at Gale crater underwent chemical weathering by chlorate and bromate brines owing to the complete absence of magnetite in drill samples containing siderite. We propose a top–down oxyhalogen brine percolation model to explain the iron mineralogy of the sulfate-rich unit at Gale crater. We conclude that siderite alteration by acidic fluids alone cannot explain the redox disequilibrium witnessed in Gale crater sediments as promulgated before and siderite weathering by oxyhalogen brines is the most likely explanation. It is highly likely that the halogen cycle on Mars is interlinked to the iron and the carbon cycle on early and current Mars.